ANALYSIS OF ISLAMIC CONSUMPTION ETHICS CRITICAL TOWARD CAUSES OF CORONA VIRUS IN WUHAN, CHINA - Ahmad Maulidizen (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
The last few days, the world was shocked by the appearance of a coronavirus outbreak that attacked China's plains. According to CNN Indonesia in February 2020, 42,500 people reported being infected with the coronavirus worldwide, 947 people died from the virus that triggered this respiratory disorder, and 25,000 were treated. This virus is known to originate from Hubei Province, precisely the city of Wuhan. Therefore, an assumption links the phenomenon of the emergence of the coronavirus with the habits of the Wuhan community that likes to consume wild animals, such as bats. So the purpose of writing this article is to find out how to analyze Islam and scholars' ethical consumption about eating bats. This research is library research with a descriptive approach, namely by describing and critically analyzing the coronavirus's causes according to Islamic consumption ethics and the scholars. Data collection methods use documentation, various articles and books. Then analyzed using content analysis, critical analysis and data analysis methods deductively, inductively and comparatively. The results of this research are there are five ethics of Islamic consumption, namely monotheism, balance, responsibility, free will and the prohibition of being royal (isrāf) and must consume ḥalāl animals and provide benefits not bring danger to human life. The scholars disagree in determining the law of consumption of bats, Shāfi’ī and Ḥambalī declare ḥarām, Mālikī declared makrūh and not until ḥarām, but not something that can be consumed, while Ḥanafī disagreed, some declare ḥalāl and some who argue not ḥalāl